Single or Divided Administration of Cisplatin Can Induce Inflammation and Oxidative Stress in Male Sprague-Dawley Rats - Brigitte Rina Aninda Sidharta; Bambang Purwanto; Brian Wasita; Vitri Widyaningsih; Soetrisno Soetrisno (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Cisplatin is one of the most potent chemotherapy drugs to treat various types of cancer, however the use of cisplatin has some the adverse effect, such as the increase of oxidative stress and inflammation by malondialdehyde (MDA) and nuclear factor kappa B (NF-kB) activation. Since the dosing of cisplatin is critical, we observed the effect of single and multiple doses of cisplatin injection on rats’ inflammation and oxidative stress level.METHODS: Total of 27 male Sprague-Dawley rats were divided into 9 sub-groups, each consisted of 3 rats. The baseline sub-group received no treatments; Group 1 (sub-group 1.1, 1.2, 1.3, and 1.4) were administered one single dose of 5 mg/kg BW/intravenously (i.v) of cisplatin; and Group 2 (sub-group 2.1, 2.2, 2.3, and 2.4) were given 0.2 mg/kg BW/i.v of cisplatin twice a week for two months. Rats were observed for their body weight, NF-kB, and MDA level based on the assigned group. RESULTS: Body weight loss was observed in the 1st week after treatment for Group 1, and 7th week for Group 2. Group 1 and Group 2 showed increasing level of NF-kB and MDA since the 1st observation, which was the 1st week and 5th week, respectively. NF-kB and MDA and levels were also significantly increasing in both groups for every week of observation (p<0.05).CONCLUSION: Cisplatin injection either in single or divided dose can induce inflammation and oxidative stress thus decrease the body weight. However, dividing cisplatin in smaller dose can delay the inflammation effect on subjects.KEYWORDS: cisplatin dose, MDA, NF-kB, body weight, inflammation, oxidative stress